2014
DOI: 10.1136/acupmed-2014-010547
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on Acupuncture in the Treatment of Schizophrenia

Abstract: 3132.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…As can be seen in Figure 1, our search resulted in 97 articles, of which 38 articles were relevant, but only 26 of those 38 satisfied the inclusion criteria and were, thus, eligible for inclusion in this review. Of the 26, 7 were randomized controlled trials [32][33][34][35][36][37][38], 12 were case studies [39][40][41][42][43][44][45][46][47][48][49][50], and 7…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen in Figure 1, our search resulted in 97 articles, of which 38 articles were relevant, but only 26 of those 38 satisfied the inclusion criteria and were, thus, eligible for inclusion in this review. Of the 26, 7 were randomized controlled trials [32][33][34][35][36][37][38], 12 were case studies [39][40][41][42][43][44][45][46][47][48][49][50], and 7…”
Section: Resultsmentioning
confidence: 99%
“…However, noting that an important distinction needs to be made between quantitative and qualitative results is important. As Bosch and colleagues [43] explained in their study, a patient with schizophrenia might still suffer from hallucinations (i.e., positive symptoms, such as hallucinations, in patients with schizophrenia [40][41][42]. Shi [42] found that particularly auricular acupuncture (i.e., on the ear) was effective in treating the auditory hallucinations of patients suffering from schizophrenia.…”
Section: Positive and Negative Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively low scores in positive and negative symptoms at T1 (and T2) seem to indicate the comparative wellness of the cohort studied [51] and as a result, one would expect to see less evidence of a reduction in the scores and improvements might be more difficult to detect [52]. Previous research has shed some doubts on the sensitivity of the PANSS in this chronic patient group in research with acupuncture [32,50,51]. Secondly, as can also be seen in Table 2, the absolute scores on the PANSS subscales (with the exception of the PANSS POS subscale) do decrease between 1.5 and 4.7 points after acupuncture treatment; however, in future research larger clinical samples are needed in order to reliably test for significance since there is not enough statistical power in the present study.…”
Section: Sleep Variable After Acupuncture After Waitlistmentioning
confidence: 97%
“…The healthy control group was not treated with acupuncture; while no clinical effect of acupuncture could be expected in healthy participants (previous research has shown that acupuncture has a modulating and normalising effect) [32,33], they were only included to establish reference values in the current cultural and geographical cohort and were only used in the tests at T1. In the patient groups, two measurements were taken: before (T1) and after acupuncture treatment or a waitlist period (T2 just after waking and evening before going to sleep [34] (Fig.…”
Section: Design Overviewmentioning
confidence: 99%